2022
DOI: 10.1186/s11689-022-09443-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of deep speech phenotyping for neurodevelopmental and genetic disorders: a conceptual review

Abstract: BackgroundSpeech is the most common modality through which language is communicated, and delayed, disordered, or absent speech production is a hallmark of many neurodevelopmental and genetic disorders. Yet, speech is not often carefully phenotyped in neurodevelopmental disorders. In this paper, we argue that such deep phenotyping, defined as phenotyping that is specific to speech production and not conflated with language or cognitive ability, is vital if we are to understand how genetic variations affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 93 publications
0
4
0
1
Order By: Relevance
“…Although heterogeneity is to some extent unavoidable in a meta-analysis, as the included studies differ in various aspects, the observed values were generally high. This heterogeneity could be explained, at least partially, by the fact that people with WS present very diverse cognitive and linguistic profiles (e.g., Mervis et al, 1999, 2000; Porter & Coltheart, 2005), and only part of this cognitive variability is explained by variation in genetics (Porter et al, 2012; Serrano-Juárez et al, 2018). Therefore, the results of our meta-analysis should be taken with caution, since they refer to WS as a whole, but certain people diagnosed with this syndrome could present a diverse pattern of lexical-semantic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although heterogeneity is to some extent unavoidable in a meta-analysis, as the included studies differ in various aspects, the observed values were generally high. This heterogeneity could be explained, at least partially, by the fact that people with WS present very diverse cognitive and linguistic profiles (e.g., Mervis et al, 1999, 2000; Porter & Coltheart, 2005), and only part of this cognitive variability is explained by variation in genetics (Porter et al, 2012; Serrano-Juárez et al, 2018). Therefore, the results of our meta-analysis should be taken with caution, since they refer to WS as a whole, but certain people diagnosed with this syndrome could present a diverse pattern of lexical-semantic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the small sample presented here, the LoF mutation seen in Child 3 yielded a milder phenotypic impact in the areas of cognition and communication compared to the missense mutation in Child 1 and the microdeletion in Child 2, though it is noted that Child 3 had more significant medical issues. The differences observed among the children also highlight the importance of deep speech and language phenotyping (Chenausky & Tager-Flusberg, 2022). Thorough assessment and reporting of both speech and language skills supports accurate diagnosis and intervention as well as improved research outcomes, especially in the description of genotype-phenotype associations.…”
Section: Discussionmentioning
confidence: 98%
“…These breakthroughs have enabled whole-genome structure and variation analysis and human phenotypic analysis. Genome-based studies have highlighted the role of common genetic variability in influencing the risk for complicated disease development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%